Isolation and Identification of Hexazinone-Degrading Bacterium from Sugarcane-Cultivated Soil in Kenya - Ngigi, Anastasiah; Getenga, za; Boga, Hamadi; Ndalut, Paul (Springer US, 2014)
The s-triazine herbicide hexazinone [3-cyclohexyl-6-dimethylamino-1-methyl-1,3,5-triazine-2,4(1H,3H)- dione], is widely used in agriculture for weed control. Laboratory biodegradation experiments for hexazinone in liquid cultures were carried out using sugarcane-cultivated soils in Kenya. Liquid culture experiments with hexazinone as the only carbon source led to the isolation of a bacterial strain capable of its degradation. Through morphological, biochemical and molecular characterization by 16S rRNA, the isolate was identified as Enterobacter cloacae. The isolate degraded hexazinone up to 27.3 % of the initially applied concentration of 40 lg mL-1 after 37 days of incubation in a liquid culture medium. The study reports the degradation of hexazinone and characterization of the isolated bacterial strain
Keywords: Hexazinone; Biodegradation; Herbicide; Liquid cultures; Enterobacter cloacae